A FUNÇÃO SOCIOLÓGICA DO [v'r' NOS SALMOS DE LAMENTAÇÃO E OS CONFLITOS DE CLASSES OCORRIDOS NO FINAL DO PERÍODO PÓS-EXÍLIO - LAGE, JOVANIR (2016)
This research is organized from the problem of the opposition between “wicked and righteous” going through the different types of texts from the Persian period under the following question: Who is the [v'r' in Israeli society, and because this term appears with greater intensity in the post-exilic period? This research aims mainly to research the reasons that influenced the introduction of [v'r' terminology “wicked” in certain psalms, such as identification of the enemy. Secondary objectives of our research are: (1) analyze the conceptual formation of [v'r' in its anti-positive feature with qyDIc;; “righteous” emphasizing the ethical axis, characterized as one of the word interpretations; (2) to study the function of the word within the Psalms of Lament, supported the exegetical study of Psalm 55; (3) to understand critically, analyzing the implications of the use of [v'r' as evil representation in the social development of the Jewish community in the post-exilic period. In our approach we intend treat such study from ethical axis, extending the research to the analysis of interpretative motivations Solidarity without Old Testament context